Arts therapies for mental disorders in COVID-19 patients: a comprehensive review - Luo, Xuexing; Zhang, Zheyu; Shi, Xiaojun; He, Caihong; Wang, Jue; Wu, Qibiao; Huang, Guanghui (Frontiers in Public Health, 2023)
Background and objective The COVID-19 global pandemic has necessitated the urgency for innovative mental health interventions. We performed a comprehensive review of the available literature on the utility and efficacy of arts therapies in treating mental health problems, with special emphasis on their deployment during the COVID-19 pandemic, aiming to provide some evidence for the application of this therapy. Methods The potential studies were systematically sourced from five authoritative databases: PubMed, Embase, the Cochrane Library, Web of Science, and the CNKI database. The evaluation of these studies was conducted based on stringent criteria, including validity, suitability, therapeutic potential, and consistency. Each piece of included literature was meticulously scored in accordance with these criteria, thus ensuring the inclusion of only the most robust studies in this review. The data from these Randomized Controlled Trials (RCTs) were carefully extracted using the PICO(S) framework, ensuring a comprehensive and systemic approach to data collection. In order to emphasize the variability in the effects of differing arts therapies on COVID-19-induced psychiatric disturbances, the sourced literature was systematically categorized and scrutinized based on distinct modalities. Results Out of the 7,250 sourced articles, 16 satisfied the inclusion conditions. The therapies were predominantly meditation (n = 7), supplemented by individual studies on color therapy (n = 3), music therapy (n = 2), and single studies on horticultural therapy, dance therapy, mindfulness and music therapy, and yoga and music therapy (n = 4 collectively). These various forms of arts therapies had a positive short to medium-term impact on the mental health of COVID-19 patients. Besides improving patients' physical and mental health, these therapies can also be employed to mitigate mental health issues among healthcare professionals. Conclusion The COVID-19 pandemic has profound and long-lasting implications for public mental health. Diverse forms of arts therapies are potentially effective in addressing related psychiatric symptoms. The integration of artificial intelligence might further enhance the efficacy and scalability of arts therapies in future implementations.